Review: Modern Management of Liver Abscess - Wadhera, Sarthak; Arora, Navneet; Dhibar, Deba Prasad (Journal of Gastrointestinal Infections, 2022)
An encapsulated collection of suppurated material within the liver is termed a liver abscess, which may be caused due to bacterial, parasitic, or fungal infection. Liver abscesses can be divided into infectious, iatrogenic, and malignant. Infection spreading through the biliary tract is the most common cause now. Escherichia coli, the most common organism causing liver abscess two decades ago, is replaced by Klebsiella pneumonia, accounting for 50 to 70% of cases in the Asian subcontinent; however, liver abscesses due to Entameba histolytica are also found quiet often in day to day clinical practice. Risk factors associated with the development of liver abscess are increasing age, male sex, presence of underlying diabetes mellitus, liver cirrhosis, continuous use of proton pump inhibitors, and immunocompromised state. Fever and abdominal pain are the typical clinical symptoms of a liver abscess. Other common symptoms include nausea, vomiting, malaise, and chills. Tachycardia, right upper quadrant tenderness, and hepatomegaly are common examination findings. USG of the abdomen is performed in all suspected cases of liver abscess and has a sensitivity of 85%. Small abscesses, less than 3 to 4 cm, can be managed with antibiotics. Percutaneous drainage can be done either by single-time needle aspiration or catheter drainage.
Keywords: amoebic liver abscess; gastrointestinal infection; liver abscess; pyogenic liver abscess; single time aspiration